DETERMINATION OF COMPUTER DEPENDENCE IN TEENAGERS - Mukhidova Gulmira Khasanovna (Web of Journals Publishing, 2025)
Currently, the need to master computer technologies at the present stage of society's development is not in doubt, however, the problem of preventing the harmful effects of the hobby of virtual technologies requires increased attention. Humanity is immersed in computers and computer networks, every day more and more people (especially children and teenagers) become addicted to computers.
Keywords: Computer addiction, addiction virtual addiction, cyberaddiction, network addiction, Internet addiction.